Wood frame house construction project in Mexico - Filio Reynoso, Oscar; Borja de la Rosa, Amparo; Fuentes Salinas, Mario; Corona Ambriz, Alejandro (Revista de la Construcción. Journal of Construction, 2017)
Building wood frame houses is viewed as an excellent alternative to meet the growing demand for housing in Mexico. The aim was to design a pinewood house construction project, based on the stud structural system, to show how to proceed when building a particular housing model. The methodology is based on RCDF-2004, NTCRCDF-2004, ONNCCE S.C. Mexican standards and construction manuals. The blueprints, area and volume were derived using the AutoCAD 2010 program. Pinewood at MC≤18%, preserved with CCA (chromated copper arsenate) salts and graded with the "Class A" industrial rule was considered. Studs were placed every 24" and plywood boards were used as bracing. As a result, a one-story dwelling with a gable roof and 74 m2 of living space was designed; the construction sequence, from the foundation (slab, chain and concrete footings) to the application of finishes and coverings (mortar and asphalt shingles), was performed. It is concluded that it is possible to properly design a wood frame house by following the recommendations and technical specifications in regulations, standards and manuals, thereby making it a practical alternative in housing construction.